Prognostic impact of matted lymphadenopathy in patients with oropharyngeal squamous cell carcinoma treated with definitive chemoradiotherapy. (December 2021) - Burningham, Kevin; Moore, William; Moon, Dominic; Avkshtol, Vladimir; Day, Andrew T.; Sumer, Baran; Vo, Dat; Bishop, Justin A.; Hughes, Randall; Sher, David J.
Highlights: Prognostic impact of matted lymph nodes depended on HPV status and smoking history. Matted lymph nodes had no impact on outcome in favorable HPV-positive disease. Matted lymph nodes were associated with inferior OS, PFS, and DM in unfavorable OPC. Abstract: Objective: To determine whether cervical matted lymphadenopathy (ML) is associated with outcomes in patients with oropharyngeal squamous cell carcinoma (OPSCC) treated with definitive chemoradiotherapy (CRT). Materials and Methods: OPSCC patients treated at our institution with CRT were included (n = 417). ML was defined by three adjacent nodes without an intervening fat plane. Patients were stratified into favorable OPSCC (p16 + with ≤ 10 pack-years smoking history) or unfavorable OPSCC (p16- and/or > 10 pack years). Primary outcomes were overall survival (OS) and progression-free survival (PFS) and the cumulative incidences of regional recurrence (RR) and distant metastasis (DM). Results: The median follow-up time for the surviving cohort was 49.9 months. In favorable OPSCC (n = 220), there were no significant associations between ML and any outcome. In unfavorable OPSCC (n = 197), ML had a significant negative impact on OS and PFS, with 3-year OS for patients without and with matted nodes at 74% and 56% (HR, 1.61, 95% CI 1.01–2.58). On multivariable Cox regression, patients with ML experienced significantly worsened OS (HR 1.65, 95% CI 1.03–2.65) and PFS (HR 1.94, 95% CI 1.28–2.93). The cumulative incidence of DM was also higher with ML (31% vs. 9%, adjusted HR 3.3, 95% CI 1.71–6.48). Conclusion: ML carries no prognostic importance in patients with favorable OPSCC. However, ML portends significantly worse outcomes in individuals with HPV-negative disease or a significant smoking history. Thus, ML may help risk-stratify this latter population for treatment intensification, but does not seem to be a contraindication for treatment de-escalation in the former.